Taxonomic notes on Prothemus Champion (Coleoptera: Cantharidae), with descriptions of two new species from China and Vietnam - Tong, Hui-Qin; Liu, Hao-Yu; Kopetz, Andreas; Yang, Xing-Ke; Yang, Yu-Xia (Zootaxa, 2024)
Prothemus longiphysus Wittmer, 1995 is considered as a junior synonym of P. sanguinosus (Farimaire, 1900). Meanwhile, P. angustioripennis (Pic, 1927), originally described in Cantharis, is removed from the synonym of P. sanguinosus and reinstated as a valid species. Besides, two new species are discovered and described under the names of P. biprominens sp. nov. and P. venustiformis sp. nov. In addition, the macrophotographs of aedeagi and female internal genitalia are firstly provided for the following species: P. sanguinosus, P. purpureipennis (Gorham, 1889), P. chinensis Wittmer, 1987, P. kiukianganus (Gorham, 1889), P. limbolarius (Fairmaire, 1900) and P. monochrous (Fairmaire, 1900). A key to the Prothemus species from Nanling National Natural Reserve, China is provided.